Gallbladder with chronic calculous cholecystitis, reactive lymphoid hyperplasia and pyloric metaplasia - Shopov, Spasimir Todorov (Indian Journal of Case Reports, 2022)
The lymphoid hyperplasia of the gallbladder is a rare condition, which can be diagnosed only by performing a histological examination. Here, we present the case of a 62-year-old woman with complaints of repeatable pain in the area of the right hypochondrium for a few months. Ultrasonography revealed chronic cholecystitis with a concrement in the lumen. A cholecystectomy was then performed. Histology shows nests of cells with lymphoid origin in the lamina propria, a multitude of lymphoid follicles and areas with pyloric metaplasia in the gallbladder wall.The case presented herein is of reactive lymphoid hyperplasia resembling a lymphoma combined with chronic cholecystitis, pyloric metaplasia, and cholelithiasis.